The Art of Useless: Fashion, Media and Consumer Culture in Contemporary China - NING ZHU (Journal of Dharma, 2025)
This review examines Calvin Hui’s The Art of Useless, a cultural study of fashion, media, and consumer culture in contemporary China from the Cultural Revolution to the globalized present. Hui reads fashion objects and their cinematic representations as archives of social memory, class formation, labor, gender, and political economy. Moving across documentary, fiction film, popular literature, exhibitions, and ethnographic materials, the book argues that fashion is a privileged site for mapping the contradictions of socialist history, post-socialist reforms, and neoliberal globalization. By placing cultural texts in dialogue with Western Marxism, psychoanalysis, and cultural theory, Hui shows how consumption, production, and waste reveal the political unconscious of contemporary China. The review highlights the book’s interdisciplinary method, theoretical richness, and contribution to Chinese cultural studies, while noting the limited comparative engagement beyond China.